Effect of The Employee Recruitment Process, Quality of Human Resources and Work Motivation on Employees Performance at Indonesian Police Criminal Investigation Agency, Forensic Laboratory Centere - Erzyanto Yukama; Meita Pragiwani; Iman Sofian Suriawinata (BPJP - STEI, 2020)
This study aims to analyze the performance of examiners of subfield document and counterfeit forensic money in Puslabfor BareskrimPolri by looking at the factor of employee recruitment, quality of human resources and motivation partially or simultaneously and the variables that have a major influence on this research. This research method is a quantitative method by processing primary data through a questionnaire given to the forensic examiner documents and counterfeit currency inspectore at the police criminal investigation center. The number of samples in this study were 73 employees. Data processing in this study using SPSS version 22 and analyzed using multiple regression analysis. The analysis used in this study includes the validity test, realibility test, nominality test, coefficient test, determinant coefficient R2, multiple regression test and t test. The results of the study show that, (1) employee recruitment influence on employee performance (2) quality of human resources has significant influence on employee performance, and (3) motivation influences employee performance.